Hepatitis E virus infection among blood donors in Hangzhou - DU Ziyun; DENG Wenjun; WU Danxiao; LIU Jinhui; DONG Jie (Zhongguo shuxue zazhi)
[Objective] To investigate the infection and characteristics of hepatitis E virus among blood donors in Hangzhou. [Methods] A total of 5 075 blood samples of blood donors from Zhejiang Provincial Blood Center from September to November 2023 were collected, including 5 037 samples with normal ALT and 38 samples with elevated ALT (>50 U/L). Enzyme-linked immunosorbent assay (ELISA) was used to detect anti-HEV IgM, anti-HEV IgG and HEV-Ag. The Fisher test and Chi-square test were used to evaluate the difference in the reactivity rates of anti-HEV IgM and anti-HEV IgG among different levels of ALT. The distribution characteristics of HEV screening in blood donors were analyzed. Univariate and multivariate logistic regression were used to analyze the susceptibility factors of anti-HEV IgM and anti-HEV IgG seropositivity, and the anti-HEV IgM-reactive blood donors were followed up by telephone. [Results] The reactivity rates of anti-HEV IgM, anti-HEV IgG and HEV-Ag in 5 075 blood samples were 0.45%, 22.98% and 0%, respectively. There was no difference in the reactivity rates of anti-HEV IgM and anti-HEV IgG among different levels of ALT (P>0.05), and the results of univariate and multivariate logistic regression analysis showed that age was a risk factor for anti-HEV IgM and anti-HEV IgG reactivity in blood donors (P<0.05), while no difference in the reactivity rates of anti-HEV IgM and anti-HEV IgG among blood donors was noticed in gender, occupation and education level (P>0.05). [Conclusion] There is a potential risk of transfusion-transmitted HEV (TT-HEV) in Hangzhou, and a cost-effective HEV screening strategy needs to be established to continue regular HEV surveillance in Hangzhou to assess the risk of infection.